Adopting internet project management to achieve sustainable development goals in the context of energy transition - Svetlana Revinova; Inna Lazanyuk (Unconventional Resources)
The article analyzes the combination of the main components of sustainable development goals that affect energy transition with the principles of Internet project management. The main gaps in methodological approaches to achieving sustainable development goals and project management are identified. The business processes of the largest Internet projects of international companies Alibaba, Amazon, Yandex, aimed at achieving sustainable development goals are analyzed. Recommendations for Internet projects have been developed, which are systematized into 2 groups of business processes: related to online and offline components of the activity. The developed recommendations are aimed at the need for a deeper specification of the priorities and goals of the project. During the assessment of the developed recommendations, it was revealed that the proposals for managing an Internet project in the context of achieving sustainable development goals and energy transition are mainly aimed at ensuring the correct and effective operation of the main element of the electronic project – the platform (website, application). The recommendations developed are of a general nature for all project management and may differ and be modified depending on the scale of the project, the scope of activity, legislation, the presence of certain problems or prospects of the region of presence. However, the application of a number of such actions and measures will improve the sustainability of the project itself, reduce its impact on the environment, improve its reputation and increase competitiveness.